187k views
1 vote
Solve x2 − 7x = −13.

1 Answer

5 votes

Answer:


(7+√(-3) )/(2) \\\\(7-√(-3) )/(2)

Explanation:

Step 1: Use the Quadratic formula to solve


x^2 - 7x = -13


x^2 -7x+13 = -13 +13


x^2-7x+13=0\\


(-b+√(b^2-4ac) )/(2a) \\(-b-√(b^2-4ac) )/(2a)


(-(-7)+√((-7)^2-4(1)(13)) )/(2(1)) \\(-(-7)-√((-7)^2-4(1)(13)) )/(2(1))


(7+√(49-52) )/(2) \\\\(7-√(49-52) )/(2)

Answer:
(7+√(-3) )/(2) \\\\(7-√(-3) )/(2)

User DaveMorganTexas
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.